Preparing veterinarians to respond to animal victims: identifying and documenting physical harm - Smith-Blackmore, Martha (Animals as crime victims, 2024)
Representation of animal victims of maltreatment in the legal process can be improved by the regular inclusion of veterinarians in the investigatory and medico-legal processes, provided veterinarians receive training on recognizing and documenting abuse and neglect. Education should cover evidence management, the judicial process, and providing expert testimony. There must also be resources provided to support the delivery of forensic exams. Legislation or regulations to require a minimum level of training in this area could be sought and enforced by state licensing boards. General practitioners may perform forensic necropsies and form expert opinions. Veterinarians should be available to assist the prosecution and defense teams alike as well as work in civil settings for potential veterinary malpractice cases and other types of torts affecting animals.